Initial establishment of Erythrina velutina Willd seedlings under water deficit: physiological and biochemical aspects - de Almeida, Débora Teresa da Rocha Gomes Ferreira; da Silva, Monalisa Alves Diniz; Gonçalves, Edilma Pereira; de Almeida, Freds Fernando Alves; Silva, Júlio César de Almeida [UNESP]; Rodrigues, Caroline Marques; Viana, Jeandson Silva (Zeppelini Editorial e Comunicacao, 2023)
For plant species to establish and survive in semiarid regions, such as the Caatinga plant domain, they need to present biochemical versatility. Thus, the objective of this study was to evaluate through physiological and biochemical indicators the sensitivity of seeds and seedlings of Erythrina velutina Willd to water deficit, as this species is used in the recovery of degraded areas in the Brazilian semiarid region. The seeds were submitted to five osmotic potentials (-0.1;-0.2;-0.3;-0.4; and-0.5 MPa), evaluating the percentage of germination (normal seedlings), germination speed index, length of aerial parts and root system, total dry mass, the concentration of photosynthetic pigments (chlorophylls a, b, and carotenoids) in aerial parts and root system, soluble carbohydrates and proteins, proline, and the enzymes ascorbate peroxidase, catalase, superoxide dismutase, peroxidase, and polyphenoloxidase. The water deficit reduced the germination speed index and percentage, aerial parts and root length, aerial parts and root dry mass, and photosynthetic pigment content in seedlings; however, there was an increase in the levels of total carbohydrate, proline, and protein, and a reduction in superoxide dismutase. The water potential from-0,4 MPa was a limiting factor for the seedling and/or seedling formation process. The direct sowing of E. velutina would only be indicated up to the potential of-0,3 MPa for the regeneration of degraded areas in semiarid regions. The species in the seedling formation stage present less biochemical plasticity to overcome limiting conditions of water availability.
Estabelecimento inicial de mudas de Erythrina velutina Willd sob déficit hídrico: aspectos fisiológicos e bioquímicos
Keywords: antioxidant enzymatic activity; biochemical adaptations; drought; mulungu; physiological adaptations